The Monty Hyams Archive: A new resource for the information history of the late twentieth century. Issue 2 (13th March 2017) - Moore, Caitlin; Robinson, Lyn
Abstract : Purpose: The purpose of this paper is to report a new resource for the study of the history of the development of information science and information services in the late twentieth century. The Monty Hyams archives include documents relating to the career of Montagu Hyams (1918-2013), the Founder of Derwent Publications, and an innovator in patents information, chemical and pharmaceutical information, and online information access. The Archive is housed in the Department of Library and Information Science at City, University of London. Design/methodology/approach: The origins and development of the Monty Hyams Archive are described, and its value examined by an initial analysis of the light it sheds on the development of Derwent's World Patents Index. Findings: The newly established Hyams Archive allows analysis of previously private and unseen documents, which reveal the fascinating and complex personalities, issues and negotiations which led to the establishment of some of the most significant information sources and access methods of the pre-internet information environment. Originality/value: The Monty Hyams Archive is a new and unique resource for the study of the development of the scientific information environment in the last decades of the twentieth century.